Battle of Mszczonów in September 1939 - Jarno, Witold (City and War, 2021)
The article describes the capture of Mszczonów by soldiers of the 31st Kaniowski Rifle Regiment on 11 September 1939. At that time, the regiment fought in isolation from its own 10th Infantry Division and retreated independently towards the Vistula. The battle fought by the regiment was one of the greatest successes of its soldiers during the September campaign of 1939, although for many years it remained in the shadow of the parallel battle on the Bzura River. Only in recent years the memory of this somewhat forgotten victory has begun to be restored. The capture of Mszczonów by the units of the 31st Kaniowski Rifle Regiment brought glory to the regiment. His actions led, albeit for a short time, to panic in the command of the German XVI Army Corps, which was not aware of the forces that took part in the fight. The soldiers of Lieutenant Colonel Wincenty Wnuk achieved a tactical success which – although it did not bring any operational benefits – nevertheless raised the declining morale. It should be emphasized that for this victory the regiment was awarded the Virtuti Militari V class in 1966.